2020
DOI: 10.33736/ijbs.3294.2020
|View full text |Cite
|
Sign up to set email alerts
|

Receptiveness of Islamic Home Financing among Malaysians: A Revisit

Abstract: This study examines the effects of the key factors influencing the intention of first-time house buyers to choose Islamic home financing products. First-time house buyers are selected since they are the major segment of Islamic banks' profit for the Islamic mortgage sector. Drawing upon the theory of planned behaviour (TPB), this study proposes a model to test the effects of attitude, subjective norm and perceived behavioural control on the intention of selecting Islamic home financing. This study also examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Meanwhile, subjective norms and perceived behavioural control significantly affect the intention of using a mortgage. Also different from the results of research conducted by Sayuti et al (2020), which shows that attitude and perceived behavioral control of the TPB are significant in determining the receptiveness of Islamic mortgage products. The results of this previous study can be a reference in measuring millennial consumers' acceptance of Islamic mortgage products in Indonesia.…”
Section: Islamic Mortgagecontrasting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, subjective norms and perceived behavioural control significantly affect the intention of using a mortgage. Also different from the results of research conducted by Sayuti et al (2020), which shows that attitude and perceived behavioral control of the TPB are significant in determining the receptiveness of Islamic mortgage products. The results of this previous study can be a reference in measuring millennial consumers' acceptance of Islamic mortgage products in Indonesia.…”
Section: Islamic Mortgagecontrasting
confidence: 90%
“…H2: Subjective norms have a positive and significant effect on an individual's intention to choose Islamic mortgage products Perceived Behavioral Control Ajzen (1991) defines perceived behavioural control as the presence or absence of the necessary resources and opportunities, as well as individual perceptions or the ease or difficulty of performing exciting behaviours. Previous empirical studies have stated arguments and indicated that PBC has a positive and significant effect on an individual's intention to choose Islamic mortgage products (Ahmed et al, 2019;Ali et al, 2017;Amin et al, 2011;Amin, Rahim, et al, 2014;Ibrahim et al, 2017;Sayuti et al, 2020). This explained that if there is adequate support and resources, choosing an Islamic mortgage will be positive and strong.…”
Section: Subjective Normmentioning
confidence: 98%
“…Moreover according to . Sayuti et al, (2020) and Shaikh and Noordin, (2020) many studies concluded that TPB constructs has a significant impact on investment intentions, but other factors such as religiosity, marketing and returns on investments also considered by some studies 3.2. Themes and Sub-themes A synthetic analysis has done to categorize the selected literature into themes (Braun and Clarke, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this model provides better insights to understanding on the lack of willingness control of an individual over the actual behaviour (Ajzen, 1991). TPB has been used in theorydriven research to examine topics such as the purchasing of halal food, sustainable housing, and the behaviour of online gamers (Sayuti et al, 2020).…”
Section: Literature Review Theory Of Planned Behaviormentioning
confidence: 99%
“…Numbers of researches have made the Islamic home financing and customer purchase intention a subject of interest (Ajetunmobi et al, 2018;M. A. Ibrahim et al, 2017a;Sayuti et al, 2020;I. M. Shaikh et al, 2021;I.…”
Section: Customers' Adoption Intention Of Islamic Home Financingmentioning
confidence: 99%